DETERMINASI FAKTOR PENENTU INVESTASI SWASTA DI SUB SEKTOR PERIKANAN PERIODE 1967-2000 - Tajerin (Jurnal Organisasi dan Manajemen, 2006)
The Indonesian government has relied more on private fisheries investment than on government investments to achieve the targeted growth of fisheries sub sector. In line with this policy, the objective of this study is to analyze factors or government policies that having important impacts on private fisheries investment in the sub sector.  Two investment annual models were specified, investments for domestic and foreign investor.  Dummy variables were specified to represent government policies related to the sub sector and Ordinary Least Square (OLS) were used to estimate the models.  The results of the study showed that the government policies, such as PAKEM (devaluation, and increasing efficiency and competitiveness) and PAKMEI (tariff reduction, and investment and export procedure simplifications), have effective effect to investment in the sub sector. Moreover, investment have been affected by interest rate and shrimp price. However, their effects are considered small, indicated by less than one elasticity coefficient. This implies that government policies will still an important factor in determining growth in the sub sector.